POLITICAL AND INSTITUTIONAL FLUCTUATIONS OF HYBRID REGIMES - Шаповаленко, М. В. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2019)
In the article the phenomenon of political and intuitions fluctuations of the hybrid political regime is investigated as a separate, intermediate type. Term the «hybrid regime» arises up within the framework transition researches of the post-authoritarian regimes in the different regions of the world. Transitologists mentioned that such regimes have traits of both authoritarian and democratic ones. The emergence of such regimes is influenced by different factors: starting from globalization and geopolitical surrounding to political establishment and population political culture, that merge between authoritarian and democratic regimes. Basic conceptual problems that arise up during the study of this type of the political regime are distinguished and analyzed. The current approaches to the typology of the hybrid political regimes are reviewed. The American political scientist L.Diamond is as early as 1996, establishing the end of the «third wave» of democratization, marked that the main reason of its «slump» was the transition of some countries not to liberal democracy but to other transitional forms of political regimes. Since then plenty of various conceptions of the so-called hybrid political regimes appeared, that testifies, from one side, high relevance and personal interest of scientific stakeholders in problems of research of intermediate types of the political regimes, and from the other side, an ambiguousness in approaches in the phenomenon conceptualization. It is related to that term «hybrid regime». It is related to that the term of «hybrid regime» needs certain research with bringing in of regional specific. In the specter of research of hybridness, or clarification of this concept there was conception of neopatrimonialism, the neopatrimonial democracy that develops the optical focusing on features of the post-soviet regimes. At the same time, this allows analyze institutes that arise up on crossing of network and systemic planes.